THE USE OF SAME-LANGUAGE SUBTITLES ON YOUTUBE VIDEOS TOWARDS STUDENTS' LISTENING COMPREHENSION: ADVANTAGES AND DISADVANTAGES - Shalihah, Andi Musfiqah; Farahdiba, Syarifah; Sofyan, Ryan Rayhana (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aims to find out the advantages and disadvantages of same-language subtitles on YouTube videos. The researcher applies the descriptive qualitative method to achieve the research objective. This research uses interview questions as an instrument of the study. The subject of this research is 6 students from the English Education Department 2019 academic year, Faculty of Languages and Literature, Universitas Negeri Makassar. The subject was chosen by using purposive sampling. The results of this research revealed that students stated the advantages of same-language subtitles include high accuracy, explaining slang, and clear punctuation. Disadvantages include inaccurate timestamps, typos, and words that are not displayed.